THE ROLE OF PLAYGROUPS IN DEVELOPING EARLY CHILDHOOD SOCIAL SKILLS - Yanthi, Winda Dwi; Fitralisma, Gian; Fata, M. Annisul; Daryati, Yeyet; Sherlin , Mei; Ardiani , Rina (Jurnal Abdisci, 2025)
Abstract: Background. The development that greatly affects character is early childhood education. One of the institutions that conducts such education is a playgroup, one of which is KOBER Srikandi in Pilang Mas Garden Housing in Kedungjaya Village. Aims. The purpose of this service is to improve the quality of teaching, learning management and increase children's physical and cognitive development. Methods. In this service activity using the implementation method which is divided into several stages, starting from planning. The second stage is preparation. Furthermore, the third is the implementation stage so that the expected goals can be achieved. KKN students follow the activities at Kober Srikandi Kedungjaya. One of them did morning gymnastics activities and helped with numbers and colors. Result. The results of Kober Srikandi management have run according to the program set. The management of playgroups in Kedungjaya Village shows that operational supervision has gone well. The playgroup program aims to improve the quality of life of the community through family development. Every education has its own goals, goals for the child's future and the child's discipline from an early age. Conclusion. This goal can be influenced by the surrounding environment, and has characteristics for the child. The better and more positive the learning environment, the more positive and enthusiastic the learning will be in the community. Implementation. According to the time sequence, childhood is a period of development from 2 to 6 years of age. Biological development at this time as in the Kedungjaya Village playgroup is rapid, but sociologically it is still very much bound by its environment and family. , the family plays a very important role in preparing children to be able to adapt to a wider environment, especially the school environment.